Economic efficiency evaluation system of maritime container terminals - Charłampowicz, Jędrzej; Mańkowski, Cezary (Ekonomia i Prawo. Economics and Law, 2020)
Motivation: Maritime container terminals play an important role in global as well as local supply chains. Especially, maritime container terminals can be perceived as essential transhipment points, which integrate other transport modes through a set of management (e.g. planning, controlling) and executive activities (e.g. reloading, handling). All these activities require the support of an adequate management system, focusing on continuous improvement of the maritime container economic efficiency. To meet this requirement an economic efficiency evaluation system is needed, which will be responsible for the assessment of maritime container terminals’ activities, mainly according to such economic criteria as time and cost efficiency. In the literature some papers can be found, which are focused on the technical efficiency evaluation systems for the maritime container terminals based on parametrical methods. However, the literature does not cover the problem of proper economic efficiency evaluation system, designed for maritime container terminals. Aim: Based on the above mentioned reasons, the purpose of the article is to develop a system of economic efficiency evaluation for maritime container terminals. Results: Based on the research findings a conceptual model of economic efficiency evaluation system for the maritime container terminals is presented in the article.